1995
DOI: 10.1074/jbc.270.51.30253
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β-Cell-specific Targeted Disruption of Glucokinase Gene

Abstract: Mice carrying a null mutation in the glucokinase (GK) gene in pancreatic ␤-cells, but not in the liver, were generated by disrupting the ␤-cell-specific exon. Heterozygous mutant mice showed early-onset mild diabetes due to impaired insulin-secretory response to glucose. Homozygotes showed severe diabetes shortly after birth and died within a week. GK-deficient islets isolated from homozygotes showed defective insulin secretion in response to glucose, while they responded to other secretagogues: almost normall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
85
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(88 citation statements)
references
References 22 publications
2
85
0
1
Order By: Relevance
“…However, glucokinase could be replaced by other insulin-independent hexokinases, in vivo and ex vivo. In vivo, knocked out mice specifically deficient in glucokinase in liver have an almost normal glucose regulation (32), whereas deficiency in pancreas glucokinase leads to neonatal death from severe insulin-dependent diabetes mellitus (33). Ex vivo, we have shown that hepatoma cells with hexokinase 1 (2, and this paper) respond to glucose in modulating transcription of glucose-responsive genes, e.g.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, glucokinase could be replaced by other insulin-independent hexokinases, in vivo and ex vivo. In vivo, knocked out mice specifically deficient in glucokinase in liver have an almost normal glucose regulation (32), whereas deficiency in pancreas glucokinase leads to neonatal death from severe insulin-dependent diabetes mellitus (33). Ex vivo, we have shown that hepatoma cells with hexokinase 1 (2, and this paper) respond to glucose in modulating transcription of glucose-responsive genes, e.g.…”
Section: Discussionmentioning
confidence: 91%
“…In endocrine pancreas ␤ cells, the predominant glucose-sensor has been definitively identified as glucokinase by knock out of the gene in mice (32,33), and the significance of the specific GLUT 2 expression in rodent ␤ cells is still disputed, especially as the amount of the GLUT 2 isoform seems to be very low in human ␤ cells (34,35). German (36) has shown that ␤ cells overexpressing GLUT 1 do not lose their ability to sense changes in glucose concentration within the physiological range and to respond by an appropriate stimulation of the insulin gene promoter.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, because human G c k + / -fetuses had decreased Gck activity in the liver, the possibility that the resultant impaired hepatic glycogen accumulation (12) may lead to alterations in fetal development cannot be excluded. In this regard, we were able to eliminate selectively the expression of the -cell isoform of Gck without affecting the expression of the liver isoform in mice by disrupting the first exon specific to the -cell type Gck (13). To understand the relationship between birth weight and fetal insulin secretion, we measured birth weight and insulin levels of neonates derived from crosses of male pancreatic -cell type Gck knockout (G c k + / -) mice (13) and female wildtype (WT) or G c k + / -m i c e .…”
Section: Y Terauchi and Associatesmentioning
confidence: 99%
“…In this regard, we were able to eliminate selectively the expression of the -cell isoform of Gck without affecting the expression of the liver isoform in mice by disrupting the first exon specific to the -cell type Gck (13). To understand the relationship between birth weight and fetal insulin secretion, we measured birth weight and insulin levels of neonates derived from crosses of male pancreatic -cell type Gck knockout (G c k + / -) mice (13) and female wildtype (WT) or G c k + / -m i c e . Low birth weight can also be associated with insulin resistance resulting from genetic defects that influence insulin action during embryogenesis.…”
Section: Y Terauchi and Associatesmentioning
confidence: 99%
“…The pancreatic GK isoform is an absolute requirement for survival, as gk del/del (either global or b-cell specific) is lethal, whereas global or b-cell-specific heterozygous (gk del/wt ) deletion causes only modest hyperglycaemia (Bali et al 1995, Grupe et al 1995, Terauchi et al 1995. Deletion of liver GK leads to mild hyperglycaemia but decreases glucose utilisation and glycogen synthesis (Postic et al 1999).…”
Section: Introductionmentioning
confidence: 99%